Healthcare reforms, inertia polarization and group influence. Issue 9 (September 2018) - Contandriopoulos, Damien; Brousselle, Astrid; Larouche, Catherine; Breton, Mylaine; Rivard, Michèle; Beaulieu, Marie-Dominique; Haggerty, Jeannie; Champagne, Geneviève; Perroux, Mélanie
Highlights: Healthcare policies are likely driven mostly by interest group preferences. Interest groups' preferences regarding healthcare reform are surprisingly consensual. In Quebec, some interest groups seem to have a veto over policy. Abstract: Healthcare systems performance is the focus of intense policy and media attention in most countries. Quebec (Canada) is no exception, where successive governments have struggled for decades with apparently intractable problems in care accessibility overall, poor performance, and rising costs. This article explores the underlying causes of the disconnection between the high salience of healthcare system dysfunctions in both media and policy debates and the lack of policy change likely to remedy those dysfunctions. Academically, public policies' evolution is usually conceptualized as the product of complex, long-term interactions among diverse groups with specific power sources and preferences. In this context, we wanted to examine empirically whether divergences in stakeholders' views concerning various healthcare reform options could explain why certain policy changes are not implemented despite consensus on their programmatic coherence. The research design was an exploratory sequential design. Data were analyzed narratively as well as graphically using a method derived from social network analysis and graph theory. Results showed striking intergroup convergence around a programmatically sound policy package centred on the general objective of strengthening primary care delivery capacities. Those results, interpreted in light of political science elitist perspectives on the policy process, suggest that the incapacity to reform the system might be explained by one or two groups' having a de facto veto in policy-making.